Konstruksi Makna Guru Sejati dalam Lakon Wayang Sang Dwija Agung Ki Purbo Asmoro: Kajian Hermeneutika - Eka Fatmawati; Sucipto Hadi Purnomo; Sungging Widagdo (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
The role of educators in learning is not only defined by teaching skills but also by their ability to develop moral and spiritual awareness. In this context, the teacher’s role can be re-examined through local cultural values, particularly in wayang performances that contain moral, spiritual, and educational symbolism. This study aims to interpret the meaning of the “true teacher” in the wayang play Sang Dwija Agung by Ki Purbo Asmoro as a reflection of Javanese thought. The analysis focuses on Rama Bargawa using Hans-Georg Gadamer’s hermeneutic approach, including historical context, pre-understanding, horizon fusion, and the hermeneutic circle. The findings show that Rama Bargawa represents a true teacher who embodies self-awareness, humility (andhap asor), honesty (blakasuta), and wisdom (wicaksana). This meaning emerges through the interpretation of dialogue within its Javanese cultural context and the fusion between text and interpreter horizons. The study confirms that the teacher’s role in Sang Dwija Agung extends beyond teaching to include guiding the ethical use of knowledge. This research offers a new perspective on Rama Bargawa as a true teacher through Gadamerian hermeneutics. In contrast to previous studies that emphasize his role as a conflict-driven figure, this study highlights his exemplary dimension, enriching the understanding of the teacher’s role in wayang studies.